Power Of An Entire Function Sharing One Value Partially With Its Derivative - Majumder, S.; Sarkar, J. (Հայաստանի ԳԱԱ)
In the paper, we investigate the uniqueness problem of a power of an entire function that share one value partially with its derivatives and obtain a result, which improve several previous results. Also in the paper we include some applications of our main result.
Keywords: Mathematics